Diseño de un sistema de gestión en la cadena de suministros, para mejorar y reducir los costes económicos en la microempresa textil DMC-STYLE. - Haro Campaña, José Andrés (2021)
This research was carried out at ‘DMC-Style’ microenterprise, located in Píllaro canton, in Marcos Espinel parish. This company is engaged in textile manufacturing and is currently experiencing problems with the acquisition of raw material, due to a change of location. It has caused the former suppliers to be long distances away and have not found the suppliers needed to fulfill the orders yet, so they have lost customers and lowered the company’s profitability. From the diagnosis made, it became evident that the organization does not have an organized supply chain system. The general objective was to design a supply chain management model for the textile microenterprise DMC-Style, in order to improve and reduce economic costs. The research has a mixed approach, since a study was conducted to evaluate, weight and interpret information obtained through surveys and interviews, processing numerical data using descriptive statistical techniques. It is an applied, descriptive, correlational and explanatory research. A study of supply chain management models was carried out, choosing SCOR for its characteristics, designing a model adapted to the company under study, providing improvements in the planning and supply processes, which made it possible to find close and reliable suppliers, eliminating shortages and providing an improvement in profitability and compliance with its commitments.